The Use of Short Movies at The Speaking Class at Al Bonafide Course - Lisa; Kiptiyah, Mariyatul (Institut Agama Islam Negeri Palopo, 2025)
This study explores the use of short movies as a learning medium in the speaking class at Al Bonafide Course. The purpose of this study was to assess the impact of using short movies on students' vocabulary comprehension, their understanding of real-life scenarios, and increased engagement and confidence in speaking. The study involved 20 third-grade students and employed a qualitative descriptive design. Data collection was done through observation and documentation. The results showed that the use of short movies can increase students' learning motivation, expand vocabulary, and improve speaking fluency. Students become more interactive, enthusiastic, and confident in expressing ideas. Although previous studies have discussed the use of short movies in language learning, this study makes a new contribution by highlighting how short movies can encourage students' interactivity and emotional engagement in the learning process. The findings support the use of short movies as an effective tool to bridge language theory and practice, making learning more dynamic and meaningful.